Furthering the implementation of AEC blueprint measures - Gilberto M. Llanto; Ramonette B. Serafica; Erlinda M. Medalla; Ma. Kristina P. Ortiz; Keith C. Detros; Fatima Del Prado; Melalyn C. Mantaring; Danica Aisa P. Ortiz; Pinky S. Padronia; Angelica B. Maddawin; Valerie Gilbert T. Ulep (Philippine Institute for Development Studies (PIDS), 2015)
The study identifies outstanding issues and bottlenecks and provides recommendations to facilitate the Philippines' full compliance to its commitments to the ASEAN Economic Community (AEC). Various in-depth interviews and surveys were conducted with concerned stakeholders from government agencies and the private sector to bring to fore the issues and bottlenecks for policymakers' action. Although its focus is mainly on services and investment liberalization, this study also tracks policy changes in trade facilitation, nontariff measures, standards and conformance, and mutual recognition arrangements after the release of the 2010/2011 AEC Scorecard Reports.
Keywords: 330; Philippines; ASEAN economic integration; AEC scorecard; services liberalization; investment liberalization; trade facilitation; non-tariff measures; standards and conformance; mutual recognition arrangements; ASEAN comprehensive investment agreement; medical professionals; maritime transport; telecommunications; tourism; banking; insurance; health services